Rôle de l’expérience professionnelle dans le milieu des soins sur les performances et la motivation des étudiants en soins infirmiers dans un dispositif hybride - Margault Sacré; Marie-Christine Toczek; Florence Policard; Guillaume Serres; Catherine Paulet; Sabine Petit; Emmanuelle Neuville; Dominique Lafontaine (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Blended learning in nursing education is currently hardly represented in the scientific literature (McCutcheon et al., 2015). However, the public of this education is unusual, especially since many of them already have a professional background in the healthcare environment. Using multiple regression models, this study aims to identify predictive variables of student performance according to their professional background. Variables related to motivation and participation were measured among 143 students in a blended course alternating videos, online formative assessments, and face-to-face supervised exercises. Results showed that participation and motivation influence their performance differently depending on whether they have prior professional experience. These results are described and discussed and could be an anchor for a scientific literature combining blended and nursing education.